Volatile organic compounds detection by electrical sensors using polyalkylthiophene-based Langmuir-Blodgett films - Silva, E. A. [UNESP]; Braunger, M. L. [UNESP]; Gregori, A.; Olivati, C. A. [UNESP] (Springer, 2019)
Despite their environmental and health hazards, volatile organic compounds (VOCs) are present in our everyday life (e.g., fuels and solvents). Their detection is of paramount importance for environmental and occupational hazards monitoring. Among other technologies, semiconducting polymers show good capabilities in VOCs detection and identification, thanks to the variation of their electronic properties upon VOC exposure. We fabricated and characterized VOCs sensors depositing thin films of regioregular poly(3-alkylthiophene) derivatives (rr-P3ATs) and stearic acid (SA) onto gold interdigitated electrodes by Langmuir-Blodgett technique. Poly(3-butylthiophene) and poly(3-hexylthiophene) (P3HT) were mixed with SA at different ratios, and their electrical conductivity was used to optimize the film composition. We characterized the optoelectronic and morphological properties of these films, as well as their electrical response to dichloromethane (DCM), tetrahydrofuran and toluene VOC exposure. Both P3AT sensors showed distinct and characteristic responses, highlighting their ability to recognize different VOCs. Moreover, we investigated the sensors saturation and sensitivity to different VOCs. The sensors were still able to detect the VOCs after six cycles, with P3HT remarkably showing no saturation at all for DCM, and the characteristic single VOC response for subsequent exposure to the different VOCs.
Keywords: Langmuir-Blodgett; Polyalkylthiophenes; Electrical conductivity; VOCs electrical sensor